Overview of debt crises in the Eurozone - experiences and lessons - Samodol, Ante; Sosa, Luka (Oeconomica Jadertina, 2024)
The subject of this paper is the European debt crisis, which is usually placed in the period 2008-2015. in which several European countries experienced the collapse of financial institutions, high national debt and large differences in yields on government bonds. The aim of the paper is to present the causes of financial crises and ways of solving and avoiding financial contagion and the collapse of the euro. The debt crisis is thought to have started in 2008 with the collapse of Iceland's banking system and then spread primarily to Portugal, Italy, Ireland, Greece and Spain in 2009, giving rise to the popular relatively insulting name (PIIGS). Peripheral eurozone member states such as Greece, Spain, Ireland, Portugal and Cyprus could not repay or refinance their national debt by the end of 2009. The banking system was on the verge of collapse, and the help of third-party financial institutions such as the European Central Bank (ECB) or the International Monetary Fund (IMF) was crucial. The crisis was eventually controlled by financial guarantees from European countries that were afraid of the collapse of the euro and the financial contagion that threatened in particular from Greece. Based on such experience, the European Stabilization Mechanism (ESM) was launched in the eurozone in 2012 as an intergovernmental organization of eurozone member states with the mission of avoiding and overcoming financial crises and maintaining financial stability. In the end, the European Central Bank (ECB) joined everything, which with its non-standard monetary policy measures since mid-2014 through asset purchase programs (APP-Asset Purchase Programs) mainly from the public sector (PSPP-Public Sector Purchase Program) with the aim of supporting the overall economic growth within the framework of inflation at the target level of 2%. Nevertheless, the inflationary shock from the beginning of 2022, combined with the energy crisis, pushed to the fore the issue of the increase in yield (interest) on the national debt against the low rates of economic growth throughout the eurozone. The purpose of the work is achieved by updating the issue of the sustainability of existing risk management models for preserving financial stability and by raising awareness about it, especially in the context of the so-called new EU fiscal rules in 2024.
Keywords: debt crisis, eurozone, national debt, Greece, Italy, Spain, Portugal, Ireland, ECB, fiscal rules